Child Bearing Women’s Knowledge and Attitude toward Health Implications of Child Binge Eating in A Nigerian Rural Community - Jafaru, Yahaya (Advances in Nursing & Midwifery, 2020)
Abstract Background: The prevalence of EDs in the general population appears to be on the rise. Binge eating disorder (BED) is characterised by frequent consumption of unusually large amounts of food. Child binge eating is an important aspect of children, now getting researchers and treatment professionals’ attention. Objective: The study was aimed at assessing the child bearing women’s knowledge and attitude toward health implications of child binge eating in a Nigerian rural community. Methods: The research was descriptive study that employed cross sectional design. Cluster method was used as a sampling procedure, and Census sampling was employed in selecting the entire child bearing women in the four selected clusters. The ethical approval for the research was obtained from Kebbi State Health Research Ethical Committee. The instrument for data collection was researcher constructed, structured, self-administered questionnaire. Data were presented in frequency and percentages. Fisher’s exact test statistical analysis was used for inferential analysis at 99% Confidence Interval. Results: majority of the respondents were knowledgeable on health implication of child binge eating in most of the questions. The questions in which majority demonstrated lack of knowledge were questions 1, 2 and 4 (67.6%, 66.9%, and 50.8%) respectively. Majority of the respondents were having negative attitude toward health implication of child binge eating. There is no statistical significant association between all the respondents’ demographic variables with the respondents’ attitude toward health implication of child binge eating; P > 0.01 respectively. Conclusions: Child binge eating as one of the factors that contribute to the development of chronic, psychological, sociological and mental diseases need to be given more attention,, and awareness about it be given to the public. Healthcare workers should provide an avenue by which the attitude of child bearing women toward child binge eating will be change to positive. Key words: Attitude, Child bearing women, Child binge eating, Implications, Knowledge